2016
DOI: 10.2337/dc16-0227
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Diabetes Therapy and Time Until A1C Goal Attainment Among Patients With Newly Diagnosed Type 2 Diabetes Who Fail Metformin Monotherapy Within a Large Integrated Health System

Abstract: OBJECTIVE"Clinical inertia" has been used to describe the delay in the intensification of type 2 diabetes treatment among patients with poor glycemic control. Previous studies may have exaggerated the prevalence of clinical inertia by failing to adequately monitor drug dose changes and nonmedication interventions. This project evaluated the intensification of diabetes therapy and hemoglobin A 1c (A1C) goal attainment among patients with newly diagnosed type 2 diabetes when metformin monotherapy failed. RESEARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 16 publications
3
70
0
Order By: Relevance
“…Overall, glycaemic response was greatest in those with poor glycaemic control, which was similarly observed in previous observational studies. In a study by Pantalone et al including patients whose HbA1c remained >53 mmol/mol (7.0%) on MET monotherapy, the level of improvement in glycaemic control was linearly associated with an increase in the baseline HbA1c level . In another recent analysis of insurance claims for patients with T2DM, where treatment failure was defined by ≄64 mmol/mol (8.0%) after a treatment with metformin monotherapy or in combination with other OADs, the change in HbA1c was greater with a higher pre‐intensification HbA1c.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, glycaemic response was greatest in those with poor glycaemic control, which was similarly observed in previous observational studies. In a study by Pantalone et al including patients whose HbA1c remained >53 mmol/mol (7.0%) on MET monotherapy, the level of improvement in glycaemic control was linearly associated with an increase in the baseline HbA1c level . In another recent analysis of insurance claims for patients with T2DM, where treatment failure was defined by ≄64 mmol/mol (8.0%) after a treatment with metformin monotherapy or in combination with other OADs, the change in HbA1c was greater with a higher pre‐intensification HbA1c.…”
Section: Discussionmentioning
confidence: 98%
“…Supporting the clinical guidelines, observational studies have consistently shown a positive association between the decrease in HbA1c and treatment intensification in patients who did not achieve glycaemic control with metformin (MET)‐based antidiabetic care . Time in clinical inertia, that is, the failure to initiate or intensify treatment when indicated, needs to be shortened to increase the likelihood of attaining glycaemic control and lower HbA1c levels . However, 52% of patients with insufficient response to MET, alone or along with another oral antidiabetic drug (OAD), experienced therapeutic inertia for ≄1 year …”
Section: Introductionmentioning
confidence: 99%
“…Patients who undergo treatment intensification at lower HbA1c levels are more likely to achieve HbA1c ≀53 mmol/mol (≀7.0%) than patients whose treatment is intensified at higher levels of glycaemia 24. Furthermore, patients who receive early treatment intensification achieve treatment goals more rapidly than those who do not, regardless of the target HbA1c level 25. Notably, in both LixiLan‐O and ‐L, iGlarLixi led to glycaemic control (HbA1c <53 mmol/mol [<7.0%]) more quickly after treatment initiation and in more patients compared with iGlar alone 26.…”
Section: Discussionmentioning
confidence: 99%
“…Using US EMR data, Rajpathak et al reported that additional oral therapy within 3 vs 10‐15 months significantly improved attainment of glycaemic goals (47% vs 42%). Pantalone et al used US EMR data to show that earlier intensification (mainly additional antidiabetes medication or titration of metformin dosage) vs after 6 months resulted in significantly faster time to A1C goal attainment. Lastly, Fu and Sheehan reported a greater A1C reduction among patients whose treatment was intensified (oral or injectable drugs) within 6 months of baseline (vs after 6 months or with no intensification) using US insurance claims data.…”
Section: Discussionmentioning
confidence: 99%